﻿Study of pharmacokinetic of new peptide drug 1-deamino-arginine-vasotocin for hypernatremia correction - Vera M. Kosman; Natalya M. Faustova; Marina V. Karlina; Valery G. Makarov; Marina N. Makarova (Belgorod National Research University, 2022)
Introduction: The pharmacokinetics studies are some of the necessary parts of the drugs preclinical investigations. Pharmacokinetic properties of new peptide drug 1-deamino-arginine-vasotocin (dAVT) in the form of an injection solution for intravenous and intramuscular administration for hypernatremia correction were investigated. Materials and methods: The study was carried out on male rats and rabbits with a single intravenous administration of the drug in three doses, a single intramuscular administration in one dose and multiple administration to rats in one dose. To determine natriiuretic peptide concentration in blood plasma, tissues, and excretes, assays based on a sodium level change measurement using a biochemical analyzer have been developed and validated. Pharmacokinetic parameters were calculated by the model-independent method of statistical moments. Results and discussion: The pharmacokinetics of the drug was found to be linear after a single administration of dAVT drug in the dose range 3-10 μg/kg for rats and rabbits. The relative bioavailability of dAVT after intramuscular and intravenous administrations was more than 30%. After a biomarker content change, the active substance was intensively distributed into highly vascularized organs (spleen), the organs that provide metabolism and subsequent excretion (liver and kidneys), whereas it hardly reached moderately and weakly vascularized tissues (muscles, omentum). Less than 10% dAVT was excreted with urine; no dAVT was determined in feces; and repeated administration did not lead to its cumulation. Conclusion: Pharmacokinetics parameters of new nonapeptide drug 1-deamino-arginine-vasotocin were evaluated after original analytical biomarker approach. The study included all main areas necessary to characterize the original drug pharmacokinetic.